2017
DOI: 10.1038/s41598-017-12066-3
|View full text |Cite
|
Sign up to set email alerts
|

Opiate use inhibits TLR9 signaling pathway in vivo: possible role in pathogenesis of HIV-1 infection

Abstract: The molecular mechanism of opiate use promoting HIV-1 infection is not fully understood. TLR9 is expressed in many immune cells, including monocytes, macrophages, which can recognize viruses and viral products and consequently induce the production of antiviral factors and initiate immune responses. Previous studies have shown that chronic viral infections can overcome and impair TLR9 pathway. We aimed to explore whether opiate use enhances HIV infection through inhibition of TLR9 pathway via a population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…This KEGG pathway has been related to enhanced HIV-1 infection [30] and morphine treatment has been shown to promote HIV-1 replication in macrophages via inhibition of the TLR9 pathway [64]. Furthermore, an increased rate of HIV-1/HTLV-I infection has been observed due to morphine in injection drug users [65]. Morphine is also associated with enhanced hepatitis C virus (HCV) replicon expression [66,67].…”
Section: Mir-3611mentioning
confidence: 99%
“…This KEGG pathway has been related to enhanced HIV-1 infection [30] and morphine treatment has been shown to promote HIV-1 replication in macrophages via inhibition of the TLR9 pathway [64]. Furthermore, an increased rate of HIV-1/HTLV-I infection has been observed due to morphine in injection drug users [65]. Morphine is also associated with enhanced hepatitis C virus (HCV) replicon expression [66,67].…”
Section: Mir-3611mentioning
confidence: 99%
“…The neural pathways involved in opioid enhancement of HIV-induced inflammation and cell death appear to involve the activation of MOP and downstream effects through PI3K/Akt and/or MAPK signal transduction ( Hauser et al, 2005 ). Recent studies by Liao et al (2017) have shown that combined with HIV-1 infection, morphine reduces the expression of MyD88, ISG56, and Mxa in macrophages by inhibiting the TLR9 pathway, which in turn promotes the replication of HIV-1 in macrophages.…”
Section: Opioids Macrophages and Hiv Infectionmentioning
confidence: 99%
“…miR-5197 is critical for mucin-type O-glycan biosynthesis pathways, which relate to both human and veterinary viral infections, including HTLV-1, Ebola, HIV-1, HSV-1, avian influenza, and avian oncogenic retrovirus [ 46 , 47 , 48 , 49 , 50 , 51 ]. miR-5197 is also related to the KEGG morphine addiction pathway, which is linked to enhanced HIV-1 infection, HCV replicon expression, the reduced clearance of pulmonary influenza virus infection in rats, and increased SAIDS in rhesus monkeys [ 52 , 53 , 54 , 55 , 56 , 57 ]. miR-5197 furthermore influences the metabolism of xenobiotics by cytochrome P450 mechanisms and the TGF-β signaling pathway, which is associated with viral entry and HIV infection [ 58 ] and is strongly linked to both pulmonary and cardiovascular diseases [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%